Economic Empowerment of Community Participants in Lazismu Banyumas Productive Program Based on Mosques - Rhis Ogie Dewandaru (Journal of Society, Community and Business Development, 2024)
LazisMu, the leadership regional of Muhammadiyah in Banyumas, operates as a non-profit entity with a clear mission: to empower the local community by effectively utilizing zakat, infaq, and wakaf funds contributed by community members. These funds are strategically allocated to support economic empowerment initiatives, with a particular focus on micro, small, and medium enterprises (MSMEs). One notable initiative is the support provided to the congregation of Masjid Al Ikhlas in Karang Tawang Hamlet, Banteran Village, Wangon District, Banyumas. This community serves as a prime example of Lazismu Banyumas' successful implementation of empowerment programs targeting farmers and MSMEs. Through this program, farmers receive valuable assistance in managing post-harvest processes, enhancing the value of their crops and ultimately improving their quality of life. The implementation of Community Science and Technology Services further aids farmers in optimizing their rice harvests to maximize profitability. Additionally, comprehensive training sessions covering various aspects such as marketing strategies, product innovation, and financial management for households and MSMEs are expected to yield tangible benefits, contributing to the overall welfare and development of the community and society at large.